2014
DOI: 10.1097/imi.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Responses after Resection for Lung Cancer via Video-Assisted Thoracoscopic Surgery and Thoracotomy

Abstract: Objective Innate immune responses to pulmonary resection may be critical in the pathogenesis of important postoperative pulmonary complications and potentially longer-term survival. We sought to compare innate immunity of patients undergoing major pulmonary resection for bronchogenic carcinoma via video-assisted thoracoscopic surgery (VATS) and thoracotomy. Methods Bronchoalveolar lavage was conducted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 25 publications
2
20
0
Order By: Relevance
“…Patients undergoing lung surgery via thoracotomy had a higher rate of postoperative complications and increased plasma concentrations of IL-6, IL-8 and IL-10. [ 18 , 19 ] In accordance with these results patients in the complication group with higher plasma concentrations of IL-6, IL-8 and IL-10 underwent thoracotomy more often (86% versus 58%). We measured IL-6 and IL-10 plasma concentrations at the time of wound closure and on the first postoperative day as most complications occur quite early on the second or even first postoperative day.…”
Section: Discussionsupporting
confidence: 72%
“…Patients undergoing lung surgery via thoracotomy had a higher rate of postoperative complications and increased plasma concentrations of IL-6, IL-8 and IL-10. [ 18 , 19 ] In accordance with these results patients in the complication group with higher plasma concentrations of IL-6, IL-8 and IL-10 underwent thoracotomy more often (86% versus 58%). We measured IL-6 and IL-10 plasma concentrations at the time of wound closure and on the first postoperative day as most complications occur quite early on the second or even first postoperative day.…”
Section: Discussionsupporting
confidence: 72%
“…[ 30 31 ] Notably, differences in nearly all of the postoperative cytokines and plasma immunomodulatory mediators measured thus far between VATS and thoracotomy groups are short-lived, in the order of hours to a couple of days. [ 7 8 ] In our study, on PODs 1, 3, 7, 30, NK cell numbers were found to be significantly higher following VATS lobectomy compared to the open approach, suggesting that VATS is associated with less inhibition and quicker recovery of NK cell than conventional thoracotomy. The rationale behind remains to be fully elucidated and actually encompasses numerous factors, including reduced acute-phase cytokine responses and postoperative pain, differences in patient expectations, and possible psychological effects.…”
Section: Discussionmentioning
confidence: 56%
“…Less immune disturbance after VATS lobectomy was previously shown in several researches on plasma immunomodulatory mediators[ 7 8 ] and NK cells. [ 30 31 ] Notably, differences in nearly all of the postoperative cytokines and plasma immunomodulatory mediators measured thus far between VATS and thoracotomy groups are short-lived, in the order of hours to a couple of days.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations